2009
DOI: 10.1007/s11250-009-9361-4
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Mycobacterium bovis-infection and atypical mycobacterioses in cattle in and around Morogoro, Tanzania

Abstract: A study was conducted to determine the prevalence of Mycobacterium bovis-infection and atypical mycobacterioses in different cattle herd management systems in and around Morogoro, Tanzania. Between April and June 2005, a total of 728 bovines from 49 herds were tested for M. bovis-infection and atypical mycobacterioses. Milk samples were taken from tuberculin positive animals and analysed for the presence of mycobacteria. Total prevalences of 2.5% and 10.1% were found for M. bovis-infection and atypical mycobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
(32 reference statements)
1
18
3
Order By: Relevance
“…Cattle could have acquired the infection through contaminated environment during grazing or at water sources. The high prevalence of NTM seen in this study in both cattle and human is even lower than the previous reports in Jos, Nigeria by Mwak et al [29] who reported a prevalence of 23.08% in humans, and also in Tanzania by Shirima et al [30] and Durnez et al [31] reported prevalence of 6% and 10% respectively in cattle. Similarly, in their study Mdegella et al [32] and Durnez et al [31] found also high prevalence of 14% and 19% of NTM in milk samples.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Cattle could have acquired the infection through contaminated environment during grazing or at water sources. The high prevalence of NTM seen in this study in both cattle and human is even lower than the previous reports in Jos, Nigeria by Mwak et al [29] who reported a prevalence of 23.08% in humans, and also in Tanzania by Shirima et al [30] and Durnez et al [31] reported prevalence of 6% and 10% respectively in cattle. Similarly, in their study Mdegella et al [32] and Durnez et al [31] found also high prevalence of 14% and 19% of NTM in milk samples.…”
Section: Discussioncontrasting
confidence: 75%
“…The high prevalence of NTM seen in this study in both cattle and human is even lower than the previous reports in Jos, Nigeria by Mwak et al [29] who reported a prevalence of 23.08% in humans, and also in Tanzania by Shirima et al [30] and Durnez et al [31] reported prevalence of 6% and 10% respectively in cattle. Similarly, in their study Mdegella et al [32] and Durnez et al [31] found also high prevalence of 14% and 19% of NTM in milk samples. Although this study did not investigate milk and its products, it is a known practice in the study area that consumption of unpasteurized milk is a very common practice; these might expose milk consumers in the study area to a great risk of infection.…”
Section: Discussioncontrasting
confidence: 75%
“…These farms can be divided into two reactor types based on the single comparative intradermal tuberculin test (SCITT) conducted in the cattle residing on the farms in 2005 and 2006 [14]. For all animals, the “current reactor status” at the moment the trapping took place was known.…”
Section: Methodsmentioning
confidence: 99%
“…In short, the organs were homogenized and decontaminated to reduce overgrowth of nonmycobacterial organisms [39], before inoculating them on culture media (Löwenstein-Jensen, Stonebrink, and Löwenstein-paratuberculosis medium [40]) and performing DNA extraction (described in [41]) and PCR (described in [14]) with inhibition check.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation